Pengaruh Innovation Terhadap Firm Performance Pada Umkm Meubeldi Kabupaten Bojonegoro - Raka Guntur Saleksa; Arif Firmansyah (Universitas Airlangga, 2014)
Innovation is needed by SMEs to survive and thrive in business also increase performance of the firm. Previous research referred to this study that the innovation has resulted in a positive effect on the performance of the firm. While this research discusses Effect Innovation Against Firm Performance In Furniture SMEs in Bojonegoro. The population in this study amounted to 306 the number of the sample that is used as much as 175 respondents. There are two hypotheses in this research, innovation with dimensions Product Innovation, Process Innovation, Market Innovation simultaneously significant effect on the Firm Performance as the first hypothesis, and Product innovation, has dominant influence significantly to the Firm Performance for the second hypothesis. The method used for the calculation and testing of linear regression analysis premises with SPSS tool 22. This study resulted in that the dimensions of Product Innovation, Process Innovation, Market Innovation simultaneously significant effect on Firm Performance and Product innovation, has dominant influence significantly to the Firm Performance so the both of hypothesis in this study is received. For further research that examines the SMEs, can use the object of another, larger study outside the furniture business, adding a secondary data without compromising the primary data to determine the performance of the company, also with other research models based on theories that support.